Walking for leisure among adults from three Brazilian cities and its association with perceived environment attributes and personal factors - Malta Deborah C; Hallal Pedro C; Hino Adriano AF; Ribeiro Isabela; Parra Diana C; Reis Rodrigo S; Gomes Grace AO; Brownson Ross C (BMC, 2011)
Abstract Background Walking is a popular form of physical activity and a convenient option to prevent chronic diseases. However, most of the evidence on this topic derives from high-income countries and little is known about walking patterns and its association with environmental features in low and middle income countries. Objectives To describe walking for leisure and to identify its association with perceived environment and personal factors among residents of three state capitals from different regions of Brazil Methods Cross sectional phone surveys were conducted in Recife, Curitiba and Vitória (n = 6,166) in 2007, 2008 and 2009 respectively. Physical activity was measured using the leisure-time sections of the long version of the International Physical Activity Questionnaire (IPAQ). Perceived environment characteristics were assessed using a modified version of the Neighborhood Environment Walkability Scale (NEWS). Multivariable analysis tested the associations between walking for leisure and perceived environment characteristics across the cities using logistic regression. Results The proportions of respondents meeting physical activity recommendations through walking for leisure were 9.6%, 16.0% and 8.8% in Curitiba, Recife and Vitoria, respectively. Engaging in 150 min/wk or more of walking for leisure was significantly associated with younger age, higher education, better self-rated health and with lack of sidewalks on nearby streets. We did not find positive associations between walking for leisure and traffic conditions and safety related to cycling/walking during the day or night. Conclusion Most environmental features were not associated with walking for leisure. Personal factors were stronger predictors of walking for leisure as compared with perceived environment factors.